Postrzeganie srebrnej gospodarki w kontekście wyzwań związanych ze starzejącą się populacją w ujęciu lokalnym : studium przypadku - Bartkowiak, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
An ageing society is a challenge of modern times. One of the areas where there is a chance for the effects of demographic processes to be mitigated, is the silver economy, widely understood as an economy that responds to the changing needs of different groups of older people. This aspect is evident in the development strategies being created at European, national, or regional levels, but to a much lesser extent at the local level. At the local level, actions are implemented that take into account the specificity of a particular social situation, that may differ significantly from the situation at higher levels. When drawing up development strategies, local governments and local opinion formers should have complex information of the demographic situation of a given territorial unit and should know the solutions applied in so-called good practices. The article presents the results of the research (case study) verifying whether the solutions related to an ageing population, implemented at the local level, take into account the use of the potential of the silver economy and the knowledge of local governments and opinion-formers in this respect. A qualitative study was applied, based on desk research, the technique of individual in-depth interviews and focused group interviews.
Keywords: silver ecomony; social policy; local development; ageing of the population